Working with emotional intelligence - Goleman, Daniel (Bantam Books New YorkUS, 2000)
Presents emotional intelligence and competence as the determning factors in the achievement of job excellence. Details 12 job capabilities based on self-mastery; looks at 13 key relationship skills including: empathy, service orientation, influence, and leadership. Offers guidelines for improving emotional intelligence capabilities; and analyses the emotionally intelligent organization.